Characterisation of carbonated Portland cement paste with optical fibre excitation Raman spectroscopy. (15th March 2017) - Yue, Yanfei; Wang, Jing Jing; Basheer, P.A. Muhammed; Boland, John J.; Bai, Yun
Highlights: A 514.5 nm optical fibre excitation Raman system was successfully established. Calcite/aragonite formed in PC paste was identified by optical fibre Raman system. There is a potential for developing a Raman-based optical fibre sensor system. Abstract: This study demonstrates the potential of developing a future Raman spectroscopy-based sensor system for monitoring carbonation of concrete structures. A tailored optical fibre Raman system was developed under the classical 45° geometry with a specific optical fibre assembly acting as the laser excitation-path. This system was then employed to characterise the calcium carbonate polymorphs, i.e. calcite and/or aragonite [ʋ1 (CO3 2− ) at 1086 cm −1 ], formed in the carbonated PC paste powder. The finding shows a good potential of optical fibre Raman spectroscopy for monitoring the health condition of concrete structures in the future.